Video Tutorials as Academic Writing and Research Support for Students of International Business - Staley, Larssyn; Göldi, Susan; Nikoulina, Anna (Journal of Academic Writing, 2020)
Many studies have made claims for the positive effects of multimedia in education; however, there is a lack of systematic and comparable research, especially when it comes to video tutorials. This study evaluates the use and benefits of short screencast video tutorials, produced with Camtasia and published on YouTube, in preparing students for research-based writing assignments. The study employs a multi-method research design, comprising an analysis of video-tutorial viewership data from YouTube and a student questionnaire on the perceived benefits of these video tutorials. The data on how the tutorials are used, as well as the questionnaire responses, enable us to highlight which aspects of these tutorials positively affect the learning process. Findings indicate that the use of such tutorials is more dependent on the type of information included (e.g., theory, instructions or examples), than their length (within the range of 3-6 min). Additionally, novice, introductory-level students appear to have received greater benefit from the tutorials than students with some previous academic writing experience.